2010
DOI: 10.2478/s11756-009-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and biochemical parameters in maternal pre-delivery and post-delivery plasma

Abstract: Lipid peroxidation (LPX) can play an important role in development of functional and pathological changes of maternal tissues in the course of pregnancy and delivery. LPX products were measured as thiobarbituric acid reacting substances (TBARS), using malondialdehyde as the standard solution. Actual TBARS determined in maternal post-delivery plasma (2.71 ± 0.602 nmol/mL) were not statistically different from those determined in pre-delivery plasma (3.45 ± 0.530 nmol/mL). TBARS production was measured in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…There is a great body of evidence that pregnancy is a physiological condition exhibiting a high susceptibility to oxidative stress development [23]. Increased oxidative stress leads to oxidative modifications of lipids, and lipid peroxidation is considered the cause of complications in pregnancy, especially in the development of preeclampsia [2,11,13,19,20]. In our study, during physiological pregnancy without complications, the examined parameters of oxidative stress have shown the following characteristics: LOOH and PAB increased significantly in early pregnancy compared to the value in the control group of non-pregnant women (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a great body of evidence that pregnancy is a physiological condition exhibiting a high susceptibility to oxidative stress development [23]. Increased oxidative stress leads to oxidative modifications of lipids, and lipid peroxidation is considered the cause of complications in pregnancy, especially in the development of preeclampsia [2,11,13,19,20]. In our study, during physiological pregnancy without complications, the examined parameters of oxidative stress have shown the following characteristics: LOOH and PAB increased significantly in early pregnancy compared to the value in the control group of non-pregnant women (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…They are important for the normal course of pregnancy and fetal development. When the balance with the antioxidant system is disturbed, oxidative stress in pregnancy may lead to serious complications, such as preeclampsia, gestational diabetes mellitus, IUGR, miscarriage and preterm birth [2,11]. Increase in oxidative stress is associated with abnormal lipid profile and may cause oxidative modification of lipids, so the studies which were conducted in complicated pregnancies also showed increased concentrations of lipid peroxides [2,12,13].…”
Section: Introductionmentioning
confidence: 99%